2017
DOI: 10.4236/ojn.2017.712100
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Understaffing of Nurses and Patient Safety in Hospitals—A Literature Review with Thematic Analysis

Abstract: Introduction: Patient safety and the occurrence of adverse events in hospitals is a topic which has been widely addressed over the last decades. In that respect, there has been an increasing interest in the effect of working conditions on patient safety, and whether understaffing and adverse events are correlated. This paper therefore reports results from a study of understaffing of nurses understood as a lack of nurses available to conduct the tasks required of them. This implies that nurses are forced to ign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Comparably, Lake et al () reported that ICU nurses with 20 or more beds experience burnout more often than those in smaller ICUs with less than 10 beds. In a literature review, Glette, Aase, and Wiig () found that a greater bed capacity means a higher workload for nurses, especially for an understaffed hospital, and a possible compromise in a nurse's ability to provide safe care. These data must be interpreted with caution because the staffing pattern was not measured in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, Lake et al () reported that ICU nurses with 20 or more beds experience burnout more often than those in smaller ICUs with less than 10 beds. In a literature review, Glette, Aase, and Wiig () found that a greater bed capacity means a higher workload for nurses, especially for an understaffed hospital, and a possible compromise in a nurse's ability to provide safe care. These data must be interpreted with caution because the staffing pattern was not measured in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although health personnel's emphasis on efficiency to deliver timely care was identified in the results of this review (Grant and Guthrie, 2018;Duncan et al, 2019;Xiao et al, 2010), efficiency may become an issue if it is continuously favored over other quality dimensions (Hollnagel, 2009). A predominant focus on efficiency may be problematic for healthcare quality (Glette et al, 2017), as well as challenging health personnel's welfare and work satisfaction; moreover, it has implications for patient safety (Glette et al, 2018;Karlsson et al, 2019). This demonstrates the importance of balancing efficiency and thoroughness, as described by the ETTO principle (Hollnagel, 2009).…”
Section: The Important Balance Between Efficiency and Thoroughnessmentioning
confidence: 99%
“…In addition to the health and financial benefits to the HCWs themselves, vaccination benefited the organization by returning HCWs to their jobs more quickly and reducing the need to hire temporary replacement staff who were likely less productive until they completed required training and learned institutional nuances. A reduced healthcare workforce can lead to increased costs based on overtime, premium shift differentials, closure of outpatient clinics and elective surgeries, and increased ambulance diversion resulting in reduced ability to accept critical admissions [ 5 ]. Our findings demonstrate that COVID-19 vaccination benefits HCWs and healthcare organizations.…”
Section: Discussionmentioning
confidence: 99%